1, 3, 5‐triazine crosslinked 2, 5‐dibromohydroquinone as new hole‐transport material in polymer light‐emitting diodes. Issue 2 (17th November 2015) - Li, Yuan; Xue, Yuyuan; Xia, Lianpeng; Hou, Lintao; Qiu, Xueqing
Abstract : Inspired by the electron‐transfer process during oxidation of phenol and its derivatives, a novel hole‐transport material (HTM) BHQTZ based on 1, 3, 5‐triazine crosslinked 2, 5‐dibromohydroquinone is spin coated as the hole‐transport layer (HTL) in polymer light‐emitting diodes and shows efficient hole‐transport properties. This result provides a promising scaffold and concept for the design and feasible synthesis of HTMs and the mechanism is based on the electron transfer during oxidation of BHQTZ, which is different from traditional electron‐transport materials based on 1, 3, 5‐triazine.